Augmentation of solar air heater effectiveness with flapped triangular-wings - Promvonge, Pongjet; Sripattanapipat, Somchai; Jayranaiwachira, Nuthvipa; Nakhchi, Mahdi Erfanian; Skullong, Sompol (My University, 2025)
An experiment was conducted to identify the optimal method for enhancing the thermal effectiveness of a solar air heater duct utilizing flapped triangular-wing (FTW) vortex generators affixed to the absorber. The wings are structured in two configurations: backward FTW (B-FTW) and forward FTW (F-FTW), each incorporating a louver-flapped opening for lowering frictional loss. This study seeks to improve the Nusselt number ratio (NuR) while lowering friction loss to optimize thermal effectiveness, hence minimizing the overall dimensions of thermal energy systems. The research findings focus on heat transmission (Nu) and frictional loss (f), encompassing thermal effectiveness across the entire range of Reynolds numbers (Re) from 5280 to 22,510. The FTW elements are configured in B-FTW and F-FTW forms, employing three relative pitches (PR = 0.75, 1.25, and 1.75) and five flap angles (θ = 0°, 35°, 45°, 65°, and 90°), while maintaining a constant attack angle (α = 45°) and a wing height ratio (BR = 1). The research findings demonstrate that the FTWs produce a significant increase in Nu contrasted to the smooth duct, which varies from 4.72 to 8.05 times, while the increase in f is approximately 13 to 68.1 times. For PR = 1.25, θ = 45°, and lower Re, the greatest thermal effectiveness factor (TEF) is roughly 2.87 for the F-FTW and 2.64 for the B-FTW, while NuR is approximately 6.98 for the F-FTW and 6.29 for the B-FTW. This implies that the largest TEF is exclusively associated with the F-FTW, and therefore, the B-FTW should be averted in practice. Additionally, correlations are established and documented for the key quantities (Nu, f, and TEF).
Keywords: Heat transfer; Solar air duct; Thermal effectiveness; Triangular wing; Vortex generator